Wittgenstein after his Nachlass - Venturinha, Nuno (History of analytic philosophy, 2010)
"In this book, leading philosophers in the field explore the rich and variable tangles that characterise Wittgensteins Nachlass, as well as their relations to his conception of philosophy"--Provided by publisher.